Characteristics of functional stability in young adolescent female artistic gymnasts - Waldron, M.; Harding, J.; Barrett, S.; Gray, A. (Journal of Human Kinetics, 2021)
The aim of this study was to determine whether young adolescent female artistic gymnasts demonstrate better functional stability than age- and sex-matched non-athletes. Different characteristics of the gymnasts` postural control were expected to be observed. Twenty-two 10- to 13-year-old healthy females (ten national-level artistic gymnasts and twelve non-athletes) participated in the study. To assess their forward functional stability, the 30-s limit of stability test was performed on a force plate. The test consisted of three phases: quiet standing, transition to maximal forward leaning, and standing in the maximal forward leaning position. Between-group comparisons of the directional subcomponents of the root mean squares and mean velocities of the center of pressure and rambling-trembling displacements in two phases (quiet standing and standing in maximal leaning) were conducted. Moreover, anterior stability limits were compared. During standing in maximal forward leaning, there were no differences in the center of pressure and rambling measures between gymnasts and non-athletes (p > 0.05). The values of trembling measures in both anterior-posterior and medial-lateral directions were significantly lower in gymnasts (p < 0.05). Both groups presented similar values for anterior stability limits (p > 0.05). The comparisons of rambling components may suggest a similar supraspinal control of standing in the maximal leaning position between gymnasts and healthy non-athletes. However, decreased trembling in gymnasts may indicate reduced noise in their postural control system possibly due to superior control processes at the spinal level. The anterior stability limit was not influenced by gymnastics training in female adolescents.